STUDI KELAYAKAN TEKNIK DAN BIAYA TERHADAP ALTERNATIF FITOREMIDIASI PADA AIR LIMBAH PENGOLAHAN KOPI - Elida Novita; Sri Wahyuningsih; Charisna Adinda (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Sidomulyo Village is one of the coffee-producing locations in Silo District, Jember Regency. The coffee processing waste is no handling. The coffee processing wastewater could potentially lead to a decrease in environmental quality. Phytoremediation is an alternative technology that can be applied because of the availability of a waste storage pond in Sidomulyo, which can to become a pool for phytoremediation. Besides, phytoremediation is a simple technology that can reduce the concentration in coffee processing liquid waste. The purpose of this study was to compare phytoremediation alternatives using the aeration, circulation, and constructed wetland (CW) system, which is the most feasible to be applied to coffee processing wastewater treatment in Sidomulyo Village based on technology and cost aspects. The stages of this research were direct surveys of respondents, comparing the efficiency of phytoremediation performance with aeration, circulation and constructed wetland (CW) systems, analysis of technical feasibility, and costs. The research results show that phytoremediation with the CW system is more than feasible than aeration and circulation systems based on technological and cost aspects. Phytoremediation application using the CW system based on the technology or technical aspects is more than feasible because it easy application and has a shorter residence time (continuity). The value of the reduction efficiency of TSS, BOD, and COD parameters in coffee wastewater treatment using phytoremediation with the CW system is sequentially 29.80; 63.75; and 63.70%. Inventory cost of constructing CW for processing coffee wastewater of Rp. 64,050,000 with a storage capacity of 82.5 m3.